Perceptions of elementary school students from public Aracaju schools on the relation of Microbiology in the daily - Carneiro, Maria Regina Pires; Silva Cisne Pessoa, Tatiana Maria; dos Santos, Deise Regina; Melo, Carlisson Ramos (Scientia Plena, 2012)
Despite being closely related to aspects of citizenship, microbiology is still neglected in primary and secondary education. Thus, this study aims to assess the students’ perception to the relationship of the microbiology in their daily lives in order that such a reflective process can contribute to the formation of students as citizens. To this end, we applied an objective questionnaire with 12 questions in student groups of 6th and 7th years in three local public schools in Aracaju. The results showed that although students use basic microbiological knowledge in their daily lives, they are not able are not able to associate these procedures to Microbiology.